Implementasi Model Pembelajaran Team Games Tournament Untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Siswa Kelas 7 di SMPN 2 Padang Panjang - Salsabilla C, Annisa; Rahmi, Ulva; N, Nora (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The problem in this research is whether the Team Game Tournament (TGT) learning model can improve the learning outcomes of Islamic Religious Education and Character Education for class VII B odd semester students at SMPN 2 Padang Panjang for the 2022/2023 academic year, where previously teachers only used the lecture method. in explaining material that makes students bored and less enthusiastic about following the learning process. The aim of this research is to determine the application of the Team Games Tournament learning model in improving the learning outcomes of Islamic Religious Education and Characteristics for class VII B students at SMPN 2 Padang Panjang in the odd semester of the 2022/2023 academic year. The results of this research show that there is an increase in learning outcomes for Islamic Religious Education and Characteristics for class VII B students, as indicated by: (1) average learning outcomes in cycle I 83.6; cycle II 81.2 experienced a decrease but student completion increased. ; and in cycle III 96; (2) learning completeness in cycle I was 80% of all students and 20% were incomplete; in cycle II 88% of students had completed and 12% had not completed; while in cycle III, students have completed 100%; (3) completeness of classical learning in cycle I was 80%, cycle II reached 88%; and cycle III reached 100%.